Educator and Student Experiences of AI Integration in Higher Education Pedagogy - Mpofu, Phumuzani; Machingauta, Tatenda Thelma; Khumalo, Nontobeko Prudence (Studies in Learning and Teaching, 2025)
This study explored educators’ and students’ experiences of integrating artificial intelligence (AI) in higher education pedagogy. Guided by Sociotechnical Systems Theory (STS) and the transformative paradigm, it examined how AI influences teaching, learning, and assessment while raising issues of equity, ethics, and academic integrity. Using a qualitative phenomenological design, data were collected through semi-structured interviews, focus group discussions, and reflective journals from 26 participants, including students, lecturers, and academic leaders. Thematic analysis identified seven themes: enhanced efficiency and professionalization; curriculum and assessment transformation; originality and academic integrity concerns; digital divide and fairness; critical thinking and independent learning; institutional preparedness and ethics; and responsible, inclusive integration. Participants acknowledged AI’s capacity to improve productivity, accessibility, and learning support but cautioned against overreliance, inequities, and ethical uncertainties. The study highlights the need for ethical AI literacy, institutional preparedness, and equitable access to technology. Its novelty lies in combining educator and student perspectives to reveal how human and technological systems co-evolve within the digital transformation of higher education.